Dinamika Organisasi Perempuan Islam: Aisyiyah dan Muslimat NU - Denisha Luthfiyah Hermawan; Rezza Fauzi Muhammad Fahmi; Yuni Nur Anggraeni; Fakhraini ‘Afi Mufidah (PT. Student Rihlah Indonesia, 2026)
This study highlights how Islamic women's organizations respond to digital disruption and the challenges of religious conservatism in Indonesia. The primary focus is to analyze the ideological and structural transformation of Aisyiyah and Muslimat NU in negotiating historical identity with the demands of modernity. The research employs a qualitative approach through a critical historiographical method, encompassing digital source heuristics, source criticism, interpretation, and contemporary historiography. Findings reveal a shift from domestic roles to strategic public engagement through enhanced digital resilience, independent philanthropy, and public policy advocacy such as the TPKS Law. The novelty of this research lies in its post-pandemic comparative-synchronic analysis, examining the use of collective memory as an instrument for social innovation. The policy implications of these findings emphasize the importance of the government positioning both organizations as strategic partners in formulating social policy and religious moderation. Theoretically, this study contributes to the repositioning of Islamic women's historiography as active subjects in the history of digital civilization in Indonesia.